PEMBAHARUAN HUKUM PIDANA MILITER DALAM PEMBAHARUAN HUKUM PIDANA NASIONAL - PH, Agustinus; Wahyuningsih, Yuliana Yuli (Jurnal Yuridis, 2014)
Renewing military criminal law should be seen as part of the efforts to reform and development of a national justice system, who in truth is a big problem faced by Indonesian to renew or replacing the colonial law. Even though reform efforts have been one long ago, at least some in 1964 to criminal law general (KUHP), but the effort was too late. Renewing military criminal law is not synonymous with renewing KUHPM reform. Renewing military criminal law is more than just a comprehensive change and renew KUHPM. Renewing military criminal law includes renewal in terms of the law (legal structure), matters of the law (legal substance),and legal cultural. Renewing military criminal law must be done by global conducted (approach), to renew the draft still formulate KUHPM with the codification its own codification KUHP on the outside.